LANGUAGE SHIFT IN KONJO COMMUNITY - Septiana, Dwiani; Yulianti, Andi Indah; Majid, Dharmawati; Rijal, Syamsul (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
One local language that is the object of preservation is the Konjo language in Bulukumba Regency. The Konjo language is interesting to study further in maintaining language to determine whether the Konjo tribe in Bulukumba Regency still maintains the Konjo language in modern life. Regency still maintains the Konjo language in modern life. This research aims to focus on sociolinguistic studies to describe the state of using Konjo language and maintaining Konjo language in the everyday life of Konjo community. The quantitative descriptive method determines how high the level of maintenance of the language under study is. Meanwhile, a qualitative descriptive method is used to describe further how the language's maintenance rate is based on a review of the causal factors. From some findings, analysis results, interviews, and field observations, the Konjo language began to experience a language shift